Immune-metabolic marker of albumin-to-fibrinogen ratio based prognostic nomogram for patients following peritoneal dialysis - Ye, Xiao-wen; Shao, Yun-xia; Tang, Ying-chun; Dong, Xiong-jun; Zhu, Ya-ning (Frontiers in Medicine, 2024)
The nutritional status and coagulation function of peritoneal dialysis (PD) patients are closely associated with their prognosis. This study aims to investigate the prognostic value of the albumin-to-fibrinogen ratio (AFR) on mortality in PD patients and to establish a prognostic prediction model based on AFR.We retrospectively collected data from 148 PD patients treated at our hospital between Oct. 2011 and Dec. 2021. Using the "survminer" package in R, we determined the optimal cutoff value for AFR and divided the patients into low-AFR and high-AFR groups. The primary endpoint of this study was overall survival (OS). Univariate and multivariate Cox analyses were used to assess the impact of AFR and other factors on prognosis, and a corresponding prognostic prediction model was constructed using a nomogram, which was evaluated through ROC curves, the c-index, and calibration plots.The optimal cutoff value for AFR was 9.06. In the entire cohort, 30 patients (20.2%) were classified into the low-AFR group. Compared to the high-AFR group, patients in the low-AFR group were older, had lower total urine output over 24 hours, higher blood urea nitrogen, higher total protein and urinary microalbumin levels, and longer remission times (P < 0.05). They also had a poorer OS (HR: 1.824, 95%CI: 1.282-2.594, P < 0.05). Multivariate Cox analysis indicated that AFR was an independent prognostic factor for OS (HR: 1.824, 95% CI: 1.282-2.594, P < 0.05). A prognostic prediction model based on AFR, age, and cause of ESRD was successfully validated for predicting OS in PD patients.Conclusions: AFR represents a potential prognostic biomarker for PD patients. The prognostic prediction model based on AFR can provide accurate OS predictions for PD patients, aiding clinicians in making better-informed decisions.